2021
DOI: 10.1111/aos.14821
|View full text |Cite
|
Sign up to set email alerts
|

Surgical techniques for primary rhegmatogenous retinal detachments between surgeons with high versus low single surgery success rates

Abstract: Background/Aims: To identify differences in preoperative characteristics and intraoperative approaches between surgeons with higher versus lower single surgery success rates (SSSR) for repair of rhegmatogenous retinal detachments (RRDs).Methods: This study is a sub-analysis of subjects who underwent RRD repair in the Primary Retinal Detachment Outcomes (PRO) study, a multi-institutional, retrospective comparative interventional study. The PRO study examined consecutive primary RRD surgeries from January 1, 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Amongst pseudophakic eyes, higher performing surgeons had graduated fellowship more recently, were less likely to use a drainage retinotomy, less likely to use PFCL, and less likely to use 360° laser retinopexy. This study suggests that there may be ‘surgeon factors’ that play a role in the success rate of primary RRD repair, and these factors may be more prominent in the repair of pseudophakic RRDs [23 ▪ ].…”
Section: Introductionmentioning
confidence: 85%
“…Amongst pseudophakic eyes, higher performing surgeons had graduated fellowship more recently, were less likely to use a drainage retinotomy, less likely to use PFCL, and less likely to use 360° laser retinopexy. This study suggests that there may be ‘surgeon factors’ that play a role in the success rate of primary RRD repair, and these factors may be more prominent in the repair of pseudophakic RRDs [23 ▪ ].…”
Section: Introductionmentioning
confidence: 85%
“…More recently, Starr et al 32 performed a multi-institutional, retrospective study of 689 rhegmatogenous retinal detachments to evaluate the differences in preoperative characteristics and intraoperative approaches between surgeons with higher versus lower single surgery success rates. The investigators reported that those surgeons with higher single surgery success rates ( > 90%) perform a higher percentage of both primary buckles and combined PPV/buckle compared with surgeons with a lower single surgery success rate (<75%).…”
Section: Outcomes Of Scleral Buckling Versus Ppvmentioning
confidence: 99%
“…27,38 These authors maintain that break localization is critical to the successful placement of the scleral buckle, and in those studies in which no difference was shown between PPV and a PPV/scleral buckle combined procedure, the buckle tends to be an encircling band placed arbitrarily at the equator. 27 It is noteworthy that in their study evaluating the techniques employed by those surgeons with high and low single surgery success rates, Starr et al 32 report that the most successful surgeons tended to both perform both more scleral buckles and more combined PPV/scleral buckle procedures than the less successful surgeons. '…”
Section: Outcomes Of Scleral Buckling Versus Ppvmentioning
confidence: 99%
“… 27 Interestingly, the PRO Study Group recently reported that surgeons with a high single surgery success rate were more likely to use an SB as part of their armamentarium in the repair of RRD compared to surgeons with a low single surgery success rate. 28 As the number of SB cases performed decrease over time, there is a risk that SB becomes a dying art and vitreoretinal surgeons in training may not be trained in SB. Non-contact wide-angled visualization with chandelier assisted SB under microscope or digitally assisted 3D surgery in addition to the new findings regarding SB and photoreceptor re-alignment may help reverse this trend.…”
Section: Introductionmentioning
confidence: 99%